2015
DOI: 10.1021/acs.jpcb.5b02093
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation Study of Skin Lipids: Effects of the Molar Ratio of Individual Components over a Wide Temperature Range

Abstract: Atomistic molecular dynamics (MD) simulations were employed to systematically investigate the effects of the molar ratio of the individual components cholesterol (CHOL), free fatty acid (FFA), and ceramides (CER) on the properties of the skin lipid bilayer over a wide temperature range (300-400 K). Several independent simulations were performed for bilayers comprised of only CER, CHOL, or FFA molecules as well as those made up of a mixture of CER:CHOL:FFA molecules in different molar ratios. It was found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(122 citation statements)
references
References 63 publications
8
114
0
Order By: Relevance
“…The CG model of skin lipid bilayer was obtained from the earlier developed united atom model32. The CG models were based on the MARTINI force field3334.…”
Section: System Models and Methodsmentioning
confidence: 99%
“…The CG model of skin lipid bilayer was obtained from the earlier developed united atom model32. The CG models were based on the MARTINI force field3334.…”
Section: System Models and Methodsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22] On the other hand, this work investigated the stability of monolayers and bilayers that are found in commercial skin care products. [13][14][15][16][17][18][19][20][21][22] On the other hand, this work investigated the stability of monolayers and bilayers that are found in commercial skin care products.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22] The bilayer membranes studied previously include those composed only of ceramides and those containing a mixture of ceramides, free fatty acids, and cholesterol. It provides molecular level information that is not accessible to current experimental techniques and, therefore, it facilitates the interpretation of experimental observations and prediction of new chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made to study the biophysical properties of key lipid components with a single bilayer for the CHARMM36 and GROMOS force fields. 52,[110][111][112][113][114][115][116][117][118][119][120] Many have focused on using three-lipid models of a ceramide, fatty acid, and cholesterol to mimic the SC. Moore et al 110 found that bilayer thickness depends strongly on the level of tail-length asymmetry and permeability strongly depends on tail-length variation.…”
Section: Example All-atom/united-atom Cell Membrane Modelsmentioning
confidence: 99%